2018
DOI: 10.1590/1678-4162-9622
|View full text |Cite
|
Sign up to set email alerts
|

Cervical relaxation for non-surgical uterus access in Santa Inês ewes

Abstract: The present study was composed by two experiments aiming to develop a cervical dilation technique for non-surgical access to Santa Inês ewe's uterus. In Experiment 1, thirty ewes underwent four epidural treatments. The three experimental treatments used 2.0mg/kg ketamine. The group receiving this drug alone was denominated KG, whereas other group had ketamine associated with 0.1mg/kg morphine (KM) and KX a third group had ketamine associated with 0.05mg/kg xylazine (KX). Control treatment was 1mL/7.5kg saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The rates of CT reached in the treated groups were similar to CT rates from other studies (81%–95%) that associated prostaglandin, oestradiol benzoate and oxytocin (Figueira et al., 2020; Fonseca et al., 2019a; Leite et al., 2018). Despite the fact that we observed no difference between the treated groups, it was possible to achieve CT rates close to 85% using only oxytocin.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The rates of CT reached in the treated groups were similar to CT rates from other studies (81%–95%) that associated prostaglandin, oestradiol benzoate and oxytocin (Figueira et al., 2020; Fonseca et al., 2019a; Leite et al., 2018). Despite the fact that we observed no difference between the treated groups, it was possible to achieve CT rates close to 85% using only oxytocin.…”
Section: Discussionsupporting
confidence: 86%
“…One strategy to overcome this difficulty in sheep is multiple ovulation and embryo transfer (MOET), in which exogenous hormones analogs (e.g. prostaglandin, oxytocin and oestradiol benzoate) are used to induce cervical dilation before attempting to transpose the cervical folds (Fonseca et al., 2016; Khalifa, Sayre, & Lewis, 1992; Leite et al., 2018). Such drugs are used because their natural analogs are involved in the physiological cascade of events that leads to natural cervical dilation, such as at oestrus and parturition.…”
Section: Introductionmentioning
confidence: 99%
“…(0.1 mg/kg; Vetnil, Louveira, Brazil) and diazepam IV (0.4 mg/kg; Teuto, Anápolis, Brazil). The test at the moment of embryo collection was also preceded by hormonal cervical dilation: Oestradiol benzoate IV (20 µg/ml; Agener União, São Paulo, Brazil) was diluted within 2.5 ml absolute ethyl alcohol and 2.5 ml saline solution and administered 12 hr prior to the moment of embryo collection; cloprostenol IM (0.12 mg; Agener União, São Paulo, Brazil) was administered at the same time; and oxytocin IV (100 IU; Centrovet, Goiânia, Brazil) was administered 15 min prior to embryo collection (Leite et al, ). An epidural anaesthetic was performed with ketamine (2.0 mg/kg; Syntec, São Paulo, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…The prostaglandin E 2 , in special, is responsible to induce smooth muscle relaxation and glycosaminoglycan production, which acts separating the collagen fibres and increasing the spaces between them, culminating with the cervical relaxation (Kershaw‐Young, Khalid, McGowan, Pitsillides, & Scaramuzzi, ). In this sense, Leite et al () have demonstrated advances in hormonal protocols for cervical dilation based on the combination of oestradiol and oxytocin previously to the TC method. Moreover, according to Oliveira et al (), the TC method is less invasive, allows animals to be used successively and has no postsurgical effects such as adherence with consequent fertility impairment.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, this method is not applicable in every condition, as it requires technician's training and experience, and the results vary widely according to the breed, parity, and the use of cervical dilation protocols. [7][8][9][10] The dilation of the cervix with hormonal protocols might facilitate NSER as these protocols usually mimic the hormonal pattern observed during oestrous/delivery. Briefly, during the follicular phase of the estrous cycle, and during the process that triggers delivery, there are increases in estradiol, PGF2α (prostaglandin F2α), and oxytocin secretion.…”
Section: Introductionmentioning
confidence: 99%